Grape pomace : an investigation into extraction techniques to enrich for different compound classes and the assessment of their biostimulant activity towards plants - Darren Nicholas, Maree (Stellenbosch : Stellenbosch University, 2023)
Darren Nicholas, Maree. 2023. Grape pomace : an investigation into extraction techniques to enrich for different compound classes and the assessment of their biostimulant activity towards plants. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/788e4383-b45d-4107-b887-57e421112e8a